HUBUNGAN MUTU PELAYANAN KEBIDANAN DENGAN TINGKATKEPUASAN PASIEN DI PUSKESMAS OEPOI DINAS KESEHATAN KOTA KUPANG - Ase Seran, Marselina; Qurrata Ayun, Sofa; Anjas Sari, Wahyu (PRIMA WIYATA HEALTH, 2023)
ABSTRACT Midwifery services are a duty and responsibility of the practice of the midwifery profession in the health care system that aims to improve maternal and child health in order to realize family and community health. The purpose of this study was to determine the relationship between the quality of midwifery services and the level of patient satisfaction at the Oepoi Health Center, Kupang City Health Office. The design used in this study is analytic with a correlation approach - cross sectional. The sample is all patients at the Oepoi Health Center, as many as 40 respondent patients. The sampling method used simple random sampling technique, with spearman rank's data analysis. The results of the research conducted showed that most of the respondents whose midwifery services were lacking were as many as 22 (55%) respondents and some of the respondents whose level of patient satisfaction was very dissatisfied were as many as 20 (50%) respondents. The results of the Spearman's rho statistical test from calculations using SPSS 16 for windows obtained a correlation coefficient of 0.744 this shows the level of closeness of the relationship between the midwifery service quality variable and the level of patient satisfaction at the Oepoi Public Health Center, Kupang City Health Office because it is located between 0.600 - 0.799 the relationship is strong while the level of the chance of error 0.01, which is smaller than the condition p < 0.05 so that it shows H0 is rejected and H1 is accepted, there is a relationship between the quality of midwifery services and the level of patient satisfaction at the Oepoi Health Center, Kupang City Health Office. The opinion through this research is that there needs to be a routine evaluation of midwife services to patients in order to be able to improve the skills and competition of midwives in supporting patient satisfaction.